Chapter 2 Aging natural or disease? A view from medical textbooks - Janac, Sarah; Clarke, Brian; Gems, David (Royal Society of Chemistry, 2017)
According to medical tradition, aging coincides with illnesses such as cancer, Alzheimer's disease and cardiovascular disease, yet is itself a 'normal', 'natural' and non-pathological process. From this perspective, anti-aging drugs are more akin to cosmetics and mind-altering drugs than to treatments in the medical sense. Yet, arguably, this traditional view of aging is incorrect. Senescence manifests as a broad spectrum of deteriorative changes, leading to debilitating and ultimately fatal pathologies. It makes little sense to speak of healthy or normal senescence: the entire process is characterized by pathology. Anti-aging drugs as a preventative approach to delay senescence fall very much within the medical remit. In this chapter we ask: Do doctors really think that aging is not a disease? And if so, why do they think this? To address the latter, we ask: What are medical students taught about the relationship between aging and disease? To this end, we analyze the contents of 14 widely used, standard textbooks of general medicine. The results suggest a general neglect of the question of what aging is, unease about the somewhat arbitrary classification of different manifestations of senescence as normal or pathological, and the absence of any rationalization of the concept of normal aging. Our findings findings findings suggest that medicine remains in the dark about aging.